How Problems Gain Importance and Become Contentious Issues through Agenda Setting - Courtney T. Owens; Alexa J. Lamm (EDIS)
A significant number of problems, like poverty, crime, and lack of resources, face people in the world today. This 4-page fact sheet discusses how a problem draws political attention through agenda setting and becomes a public issue, discusses the role the media plays in agenda setting, and provides a brief commentary on the influence of interest groups on public issues. Written by Courtney T. Owens and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, December 2014. (Photo: iStock/Thinkstock)